2015
DOI: 10.4081/ijas.2015.3770
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Processing on Amino Acid Racemization and Protein Quality in Processed Animal Proteins of Poultry Origin

Abstract: Re-authorization of processed animal proteins (PAPs) in EU, derived from by-products of human food production, could increase manufacturing of proteins for feed ingredients and reduce the need of imported proteins mainly of plant origin. The PAPs production is largely done by the rendering process during which authorized animal by-products are heat treated to extract valuable protein and animal fat, ensuring sterilizing conditions of raw incoming materials. Proteins exposure to certain processing conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…These losses could be nutritionally detrimental since these EAA cannot be synthesized by fed animals. This is in support of Papadopoulos (1989) and Bellagamba et al. (2015) who concluded that heat processing of feedstuff causes the racemization of amino acids and the formation of cross-linkages with resultant reduction in amino acid digestibility.…”
Section: Discussionsupporting
confidence: 81%
“…These losses could be nutritionally detrimental since these EAA cannot be synthesized by fed animals. This is in support of Papadopoulos (1989) and Bellagamba et al. (2015) who concluded that heat processing of feedstuff causes the racemization of amino acids and the formation of cross-linkages with resultant reduction in amino acid digestibility.…”
Section: Discussionsupporting
confidence: 81%
“…Further, over-processing might have resulted in the isomerization of l -AA into d -AA and mesoisomers which are poorly digested and unavailable for absorption ( Finot, 2005 ). Cross-linking of peptide bonds between a carbonyl group and amino group (Mallard reaction) during such severe heating processing is another possibility ( Heck et al., 2013 , Bellagamba et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short-chain peptides and certain amino acids, such as phenylalanine, have been reported to increase the production of endogenous auxin by functioning as signaling molecules, resulting in favorable effects on roots and improved vegetative growth [20,40]. The presence of small quantities of cysteine (0.79%) and threonine (2.42%) in CFPH may have resulted due to the aggressive reaction of alkali that ended up in the loss of these amino acids [41]. The peptides and amino acids present in the PH might be directly occupied by plants through the roots and leaf, reaching the target tissues and potentially acting as plant biostimulants [11].…”
Section: Production and Characterization Of Cfphmentioning
confidence: 99%